Mycelium-based composite: a way forward for renewable material - Mohd Fairus, Mariam Jamilah; Kamal Bahrin, Ezyana; Arbaain, Enis Natasha Noor; Ramli, Norhayati (Universiti Malaysia Terengganu, Malaysia, 2022)
The fluctuation of petroleum prices, fast depletion of fossil resources and environmental problems are caused by polymer derived from petroleum or natural gas due to its non-renewable and non-biodegradable properties. Recently, the industry has emphasised designing sustainable biocomposite using eco-friendly, renewable, biodegradable and low energy consumption during the manufacturing process. This target can be obtained by producing a mycelium-based composite that uses the fungal mycelium matrix to bind composite material. Agricultural waste such as lignocellulosic biomass has a great potential to be converted into the mycelium-based composite. Fungal mycelia act as a natural adhesive or binder that binds together all particles of lignocellulosic biomass during fungal colonisation. The mycelium growing phenomenon is manipulated to produce the mycelium-based composite. Therefore, the selection of suitable fungi and type of lignocellulosic biomass is essential for good mycelial network development. This will pave the way for the mycelium-based composite from lignocellulosic biomass for its use in various applications.